2003
DOI: 10.1038/sj.bjc.6600838
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of targeted α therapy for breast cancer using 213Bi-labelled-plasminogen activator inhibitor type 2

Abstract: The control of micrometastatic breast cancer remains problematic. To this end, we are developing a new adjuvant therapy based on 213 Bi-PAI2, in which an a-emitting nuclide ( 213 Bi) is chelated to the plasminogen activator inhibitor-2 (PAI2). PAI2 targets the cellsurface receptor bound urokinase plasminogen activator (uPA), which is involved with the metastatic spread of cancer cells. We have successfully labelled and tested recombinant human PAI2 with the a radioisotope 213 Bi to produce 213 Bi-PAI2, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
(29 reference statements)
2
51
0
1
Order By: Relevance
“…16). a-PAI-2 was shown to specifically kill uPA-expressing tumor cells in vitro in a dose-dependent manner (16,17) and to be efficacious in preliminary studies using mouse models of human tumors (17,18). Radio-iodinated PAI-2 has also been shown to localize in human colorectal uPA-expressing tumor xenografts in nude mouse models (19), thus providing proofof-principle data for the uPA-targeting capability of PAI-2.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…16). a-PAI-2 was shown to specifically kill uPA-expressing tumor cells in vitro in a dose-dependent manner (16,17) and to be efficacious in preliminary studies using mouse models of human tumors (17,18). Radio-iodinated PAI-2 has also been shown to localize in human colorectal uPA-expressing tumor xenografts in nude mouse models (19), thus providing proofof-principle data for the uPA-targeting capability of PAI-2.…”
Section: Introductionmentioning
confidence: 95%
“…At this stage, the animals were euthanized (overdose of inhaled CO 2 ) and the internal organs were macroscopically examined for signs of toxicity. Because previous studies found no toxicity associated with the targeting agent PAI-2 (7,17,18) and biodistribution of the radiolabeled compound to major organs was limited to the kidneys and liver (19), histologic assessments were restricted to these organs and one lymphoid organ, the spleen. Blood smears were taken and blood was also collected into K3 EDTA and Z serum gel minicollect tubes (Greiner Bio-one) for hematology and serum blood biochemistry to complete the toxicologic assessment.…”
Section: Toxicity Studies For Determination Of Maximum Tolerated Dosementioning
confidence: 99%
“…The procedure for uPA staining is published elsewhere. 25,26 Pharmacokinetics. ARC Swiss nude mice were injected with 213 Bi-PAI2 chelated with CHX-A˝ and cDTPA in different activities (range 1.18-11.84 MBq).…”
Section: Single Dose Efficacymentioning
confidence: 99%
“…[23][24][25][26] In this paper we investigate the growth of the tumor xenograft model by observing the tumor capillary development using CD31 staining at different stages of tumor growth. The in vivo organ uptake and pharmacokinetics/biodistribution for 213 Bi-PAI2 in mice using two chelators (cyclic dianhydride of DTPA and a DTPA derivative CHX-A˝) is also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation